2015
DOI: 10.1016/j.alit.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Common food allergens and their IgE-binding epitopes

Abstract: Food allergy is an adverse immune response to certain kinds of food. Although any food can cause allergic reactions, chicken egg, cow's milk, wheat, shellfish, fruit, and buckwheat account for 75% of food allergies in Japan. Allergen-specific immunoglobulin E (IgE) antibodies play a pivotal role in the development of food allergy. Recent advances in molecular biological techniques have enabled the efficient analysis of food allergens. As a result, many food allergens have been identified, and their molecular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(155 citation statements)
references
References 207 publications
4
135
0
9
Order By: Relevance
“…These results are probably because OM is resistant to heat or digestion (Urisu et al, 1997;Kovacs-Nolan et al, 2000), because OVA is the dominant protein in egg white (Benhamou et al, 2010), and because OT is a heat-labile and digestible allergen (Matsuo et al, 2015). The findings of IgE reactivity to denatured OT in this study were similar to a previously reported immunoblotting analysis using human sera (Martos et al, 2013), and OT in which most of epitopes are probably conformational loses IgE-binding capacity when linearized (Mine and Yang, 2008;Järvinen et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…These results are probably because OM is resistant to heat or digestion (Urisu et al, 1997;Kovacs-Nolan et al, 2000), because OVA is the dominant protein in egg white (Benhamou et al, 2010), and because OT is a heat-labile and digestible allergen (Matsuo et al, 2015). The findings of IgE reactivity to denatured OT in this study were similar to a previously reported immunoblotting analysis using human sera (Martos et al, 2013), and OT in which most of epitopes are probably conformational loses IgE-binding capacity when linearized (Mine and Yang, 2008;Järvinen et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Recently, it was shown that γ-, α/β-, ω5-, ω1,2-gliadins contain IgE-binding epitopes as well as HMW and LMW subunits of glutenin [99] (Table 4). Nevertheless, major allergenic protein of wheat is ω5-gliadin possessing N -terminal sequence SRLL, which can be crucial for allergy pathogenesis, and repetitive region consists almost entirely of peptides FPQQQ and QQIPQQ [14].…”
Section: Gluten Intolerance Pathogenesismentioning
confidence: 99%
“…Selection of protein and peptide targets necessarily begins with the selection of one or more food allergens of interest as shown in Figure 1. For the big eight food allergens, which are responsible for a majority of allergic reactions, the proteins responsible for clinical reactivity are generally well understood 68,69 and are often abundant within the food. For example, 94% of egg-allergic individuals were sensitized to egg white protein Gal d 2 (ovalbumin), 70 which comprises 54% of egg white protein; 71 45–87.5% of peanut-allergic individuals were sensitized to Ara h 3 (an 11S globulin), 72,73 which comprises ~30% of peanut protein; 74 85–100% of peanut-allergic individuals were sensitized to Ara h 2 (a 2S albumin), 72,75 which comprises roughly 10% of peanut protein; 74 and over 85% of milk-allergic individuals were sensitized to the dominant casein protein fraction in milk.…”
Section: Allergenic Protein and Peptide Target Selection In Msmentioning
confidence: 99%